2019
DOI: 10.2478/asn-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Bacteriological Activity of Zinc Oxide and Copper Oxide Nanoparticles

Abstract: Interest in nanomaterials, especially metal oxides, in the fight against resistant and constantly changing bacterial strains, is more and more expressed. Their very high reactivity, resulting from their large surface area, promoted them to the rank of potential successors of antibiotics.Our work consisted of the synthesis of zinc oxide (ZnO) and copper oxide (CuO) in the nanoparticle state and the study of their bactericidal effect on various Gram-negative and Gram-positive bacterial strains.The nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The difference in resistance or sensitivity may be due to cell wall structural differences, metabolism, physiology and magnitude of contact of microbes with nanoparticles (Gopalakrishnan et al, 2012). Merah et al, (2019) described similar results of CuO NPs which showed enhanced efficacy on gram negative as that of gram-positive bacteria that would be probably owing to size difference and due to Zn 2+ and Cu 2+ characteristics. Less efficacy of CuO NPs on gram positive bacteria may be due to augmented multi drug resistance.…”
Section: Discussionmentioning
confidence: 58%
“…The difference in resistance or sensitivity may be due to cell wall structural differences, metabolism, physiology and magnitude of contact of microbes with nanoparticles (Gopalakrishnan et al, 2012). Merah et al, (2019) described similar results of CuO NPs which showed enhanced efficacy on gram negative as that of gram-positive bacteria that would be probably owing to size difference and due to Zn 2+ and Cu 2+ characteristics. Less efficacy of CuO NPs on gram positive bacteria may be due to augmented multi drug resistance.…”
Section: Discussionmentioning
confidence: 58%
“…In recent years, nanoparticles play crucial role in food preservation and packaging. In the present investigation, the ZnO nanoparticles were synthesized using wet chemical approach [24]. The structural characterization of ZnO nanoparticles were carried out using X-ray Diffractometer.…”
Section: Mechanistic Study Of Antibacterial Properties Of Chemically mentioning
confidence: 99%